A Monthly Water Balance Model for Vineyard Planning and Inter-Row Management - Maria Costanza Andrenelli; Sergio Pellegrini; Claudia Becagli; Alessandro Orlandini; Rita Perria; Paolo Storchi; Nadia Vignozzi (Agronomy)
Vineyard is one of the most complex and vulnerable agroecosystems, and ongoing climate change makes it necessary to identify effective management and adaptation practices. For this reason, a water balance model tailored for viticulture was developed to be implemented within a Decision Support System (DSS) aimed at supporting winemakers both in the vineyard’s planning and management phase. Starting from a simple monthly water balance, based on the Thornthwaite–Mather method, the model returns the water stress risk class through the connection to a soil and climate database; the user can however customize the response by inserting information related to a specific vineyard (e.g., planting, soil, and management layout). The model was tested using data from a three-year field experiment carried out in a vineyard under permanent grass cover (PG) or continuous tillage (CT), allowing for the evaluation of its performance in terms of water balance estimation. The model provided results consistent with the measured soil moisture values, and the annual risk of water stress corresponds to what was measured in the field, differing at most by only one class. The model can guide the user in finding the best solutions for designing new vineyards or managing the inter-row by simulating the adoption of different strategies (trellis system, planting density, type of cover crop or soil tillage) or suggesting alternative solutions (needs of irrigation supply, more suitable cultivars, or rootstocks).